Mezclas etanol-gasolina como combustible de motores de encendido por chispa - Rodríguez Luis Arnoby; Ray Long Bill (Acta Agronómica)
In the Agricultural Mechanics Shop at Texas A&I University in Kingsville (TX), six ethanolgasoline blends (0, 20, 40, 60, 80 and 100% ethanol) were used to operated a six-cylinder engine at different operating conditions of air-fuel ratio, timing, load and speed. A main jet the carburator was used for each fuel to obtaining its stoichiometric air-fuel ratio. The main jet diameter was enlarged 1262 times from gasoline to ethanol. To select the optimun timing, timing was varied from Oto 26° BTOC (Before Top Oead Center) and the engine tes1ed at maximun power. The optimun advance timings were respectively 6, 6, 10, 14, 18 and 220 BTOC. It was not necessary to introduce modifications to operate the engine with blends containing upto 20 % ethanol. For blends with more than 20% ethanol, the advance timing (V) and the ethanol conmnt (X), followed the relation V = 2.0 + 02 X. In the last test, the engine was set at the optimun advance timing for each fuel. All the fuels performed in the same way. They followed the s e characteristic curves for power, torque, specific fuel consumption and efficiency with the following differences from gasoline to straight ethanol: maximun power and torque decreased 10.6% and 8.7% respectively; specific fuel consumption and efficiency increased 49% and 5.2%. En el Taller de Mecánica Agrícola de Texas A&T University en Kingsville (TX), se usaron seis mezclas etanol-gasolina (0,20,40,60,80 y 100% etanol) para operar un motor de seis cilindros variando la razón aire-combustible, avance de encendido, carga y velocidad. Con cada combustible se usó una tobera principal para obtener su razón estequiométrica. De gasolina a etanol el diámetro de la tobera se aumentó 1262 veces. El avance de la chispa se varió entre 0 y 26° APMS (Antes de Punto Muerto Superior). Se seleccionó como óptimo el avance al que el motor desarrolló máxima potencia. Los avances óptimos fueron 6, 6, 10, 14, 18 y 22° APMS. No fue necesario introducir modificaciones para operar el motor con mezclas que contenían hasta 20% etanol. Para mezclas con más de 20 % etanol, el avance de encendido (V) y el contenido de etanol (X), siguieron la relación V = 2.0 + 0.2 X. En la prueba final, el motor se sincronizó con el avance óptimo para cada combustible. En todos los casos, el motor se comportó en igual rma, siguiendo las mismas curvas características de potencia, par torsor, consumo específico de combustible y eficiencia, con las siguientes diferencias de gasolina a etanol: decrecieron la máxima potencia (10.6%) Yel máximo par torsor (8.7%) Y aumentaron el consumo específico de combustible (49%) Y la eficiencia (52%).